Engineering the crystallization behavior of CsPbBr3 quantum dots in borosilicate glass through modulating the glass network modifiers for wide-color-gamut displays. Issue 8 (July 2022) - Si, Shuaichen; Yu, Jinbo; Lou, Sunqi; Lan, Bang; Zhang, Jinhui; Zhang, Xuejie; Li, Man-Rong; Huang, Lin; Wang, Jing
Abstract: The in-situ growth of CsPbBr3 perovskite quantum dots (QDs) inside glass has been regarded as an alternative approach to improve their stability. Alkaline-earth metal oxides has multiple effects on the structure of the glass network. Herein, four types of alkaline-earth metal oxides are introduced into borosilicate glasses to modulate glass network structure, which has quite different effects on the crystallization behavior of CsPbBr3 QDs. The reason can be ascribed to the different impacts of alkaline-earth metal on phase separation, nucleation, and growth procedure. Moreover, CsPbBr3 QDs embedded in glass (CsPbBr3 QD@glass) exhibit superior thermostability and photostability compared with CsPbBr3 QDs powder. Finally, a white light-emitting diode achieving 124% of National Television System Committee (NTSC) gamut is fabricated using the CsPbBr3 QD@glass, K2 SiF6 :Mn 4+ phosphor film, and blue chip-on-board. This work provides a reference for modulating the glass network modifiers to regulate the crystallization behavior of perovskite QDs. Graphical Abstract: ga1